Performance of a computer-based communication system in the water and wastewater treatment plants - Khoo, Ean Lay. (2008)
The advent of the computer-based communication systems has catered to the requirement of the distributed control and automation systems in the water and wastewater treatment plants. Today, there is a myriad of computer-based communication systems installed in this industry, each with their own characteristics, strengths and weaknesses, tailored case-by-case to each application.